CONCEPT OF PRESERVING SAṂSKṚTI RAKṢAṆA CULTURE - Sunardy Kasim; I Made Gede Arimbawa; Udayana, Anak Agung Gde Bagus; Sujana, I Wayan (International Journal of Social Science, 2024)
Draft Saṃskṛti Rakṣaṇa offers a multidimensional approach to preserving traditional culture, which integrates three main elements, namely Kala (Art), Tantra (System or Method), and Adhyayana Mārga (Way of Learning). The synergy between these three elements creates a framework that is systematic, structured and adaptive to changing times, with the aim of strengthening cultural preservation and sustainability. Art, as a medium for cultural expression, not only documents but also celebrates diverse cultural values ​​through various forms of traditional art. Tantra provides the methodological basis necessary to preserve and disseminate cultural elements, including the development of scientifically accessible archives, curricula, and ethnographic techniques. Meanwhile, Adhyayana Mārga emphasized the importance of inclusive and flexible learning methods, accommodating various learning styles and utilizing digital technology in disseminating cultural knowledge. These three elements work synergistically to build a holistic cultural preservation ecosystem, which is not only relevant to the contemporary context but is also able to respond to the challenges of the times, guarantee sustainable preservation, and ensure the transfer of cultural knowledge to future generations. Thus, Saṃskṛti Rakṣaṇa provides an integrated approach in responding to the challenges of cultural preservation in the ever-developing modern